Inverse-design magnonic devices - Qi Wang (Nature Portfolio, 2021)
Inverse design is a recent development in photonics, where by locally controlling the refractive index in a matrix, nearly any information processing functionality can be achieved. Here, Wang et al. present a scheme for inverse design for spin-waves, magnons, which have a variety of unique advantages, such as short wavelength, and large non-linearity.